2018
DOI: 10.1128/jvi.00006-18
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase 1α Mediates the Degradation of Receptors for Type I and Type II Interferons Caused by Hemagglutinin of Influenza A Virus

Abstract: Although influenza A virus (IAV) evades cellular defense systems to effectively propagate in the host, the viral immune-evasive mechanisms are incompletely understood. Our recent data showed that hemagglutinin (HA) of IAV induces degradation of type I IFN receptor 1 (IFNAR1). Here, we demonstrate that IAV HA induces degradation of type II IFN (IFN-γ) receptor 1 (IFNGR1), as well as IFNAR1, via casein kinase 1α (CK1α), resulting in the impairment of cellular responsiveness to both type I and II IFNs. IAV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 75 publications
0
54
1
Order By: Relevance
“…Increasing evidence suggests that the manipulation of host cell CK1 signalling pathways by intracellular pathogens, either by exploiting host CK1 or by exporting the CK1 of the pathogen into the host cell might play an important role in infectious diseases [12] [13] [14] [15] [16]. Indeed, host CK1 pathways are vital for Mycobacterium [15].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests that the manipulation of host cell CK1 signalling pathways by intracellular pathogens, either by exploiting host CK1 or by exporting the CK1 of the pathogen into the host cell might play an important role in infectious diseases [12] [13] [14] [15] [16]. Indeed, host CK1 pathways are vital for Mycobacterium [15].…”
Section: Introductionmentioning
confidence: 99%
“…CK1α phosphorylates type I interferon receptor 1 (IFNAR1) at Ser535 and thereby induces its ubiquitination and degradation via recruitment of β-TrCP E3 ubiquitin ligase in response to endoplasmic reticulum stress as well as infection [ 137 , 138 ] by the protozoan Leishmania major or vesicular stomatitis virus (VSV) in human cells [ 137 ] and by infectious bursal disease virus in chicken [ 139 ]. Newly research have demonstrated that CK1α mediates degradation of IFNAR1 and type II IFN (IFN-γ) receptor 1 (IFNGR1) caused by hemagglutinin of influenza A virus (IAV) [ 140 ]. CK1α also acts as a specific host factor and is required for the spread of Listeria monocytogenes between cells, which occurs via formation of productive membrane protrusions [ 141 ].…”
Section: Introductionmentioning
confidence: 99%
“…HA promotes the phosphorylation and polyubiquitination of IFNAR1, leading to an efficient degradation of IFNAR1 and attenuation of the type I IFN-induced antiviral signaling pathway (Xia et al, 2016). Furthermore, HA induces the degradation of type II IFN receptor 1 (IFNGR1), as well as of IFNAR1, resulting in the impairment of the cellular response to both types I and II IFNs (Xia et al, 2018). Mechanistically, the phosphorylation and ubiquitination of IFNGR1 and IFNAR1 mediated by the cellular kinase CK1α contribute to the HA-induced elimination of type I and type II IFN receptors (Xia et al, 2018).…”
Section: Role Of Ptms In Viral Resistance To Host Ifn Responses Mediamentioning
confidence: 99%
“…Furthermore, HA induces the degradation of type II IFN receptor 1 (IFNGR1), as well as of IFNAR1, resulting in the impairment of the cellular response to both types I and II IFNs (Xia et al, 2018). Mechanistically, the phosphorylation and ubiquitination of IFNGR1 and IFNAR1 mediated by the cellular kinase CK1α contribute to the HA-induced elimination of type I and type II IFN receptors (Xia et al, 2018).…”
Section: Role Of Ptms In Viral Resistance To Host Ifn Responses Mediamentioning
confidence: 99%